Obtenção por colagem de fita aquosa de eletrólitos planos de zircônia estabilizada com ítria - Goulart, Celso Antonio (Universidade Federal de São Carlos, 2016)
Solid Oxide Fuel Cells (SOFCs) are energy conversion devices, capable of generating clean and renewable energy with high efficiency, and regarded as one of the enabling key technologies for future hydrogen economy and stationary power generation. The state of the art consists of cells with Yttria-Stabilized Zirconia (YSZ) as electrolyte and a planar design. Planar electrolytes can be obtained employing several techniques, however, tape casting is a wellestablished, low cost ceramic forming process, and almost one of the few that can be applied to manufacture ceramic sheets of controlled thickness with large areas. Organic solvents have been widely used in tape casting, but due to health, safety, disposal, cost and environmental issues, researches are focusing on aqueous systems, seeking the benefits of using water as solvent, since it is widely available, non-toxic, non-flammable and cheap. In this study, the optimization of slurry formulation and the systematic analysis of processing variables allowed the successful use of aqueous tape casting for obtaining green tapes with good mechanical characteristics (tensile strength - 11.7-12.5 MPa, strain to failure - 64- 49%) and homogeneous green microstructure with no laminating step. In turn, the sintered tapes showed homogeneous microstructure and high density (≈ 97% of theoretical density), with good mechanical and electrical characteristics (fourpoint flexural strength - 266 MPa, electrical conductivity - 4.42x10-2 S.cm-1 at 800°C), which enables their use as electrolytes in Solid Oxide Fuel Cells.
Obtention of planar electrolytes of yttria stabilizedb zirconia by aqueous tape casting
Keywords: CaCOS; Zircônia estabilizada com ítria; Colagem de fita aquosa; Processamento cerâmico; ENGENHARIAS::ENGENHARIA CIVIL